Integration of Artificial Intelligence in Teaching and Learning Visual Arts Subject in Secondary Schools - Azman, Ainul Aqidah; Rozali, Mohd Zulfadli (Online Journal for TVET Practitioners, 2026)
The use of the Technology Acceptance Model (TAM) is commonly employed in studies related to the application of technology by previous researchers. This study also adopts the TAM to examine teachers' perceptions regarding the use of artificial intelligence software in the teaching and learning process of Visual Arts Education. The aim of this study is to identify teachers' views on the utilization of artificial intelligence technology in the teaching and learning of Visual Arts Education at the secondary school level. The study is descriptive in nature, utilizing a survey method with a Likert scale questionnaire as the instrument. A total of 87 respondents, consisting of Visual Arts Education teachers in secondary schools in the Batu Pahat district were involved in this study. The findings indicate that teachers' perceptions of the ease of use, usefulness, and attitude towards the use of artificial intelligence software in the teaching and learning of Visual Arts Education at the secondary school level are high.